2015
DOI: 10.1007/s40618-015-0335-2
|View full text |Cite
|
Sign up to set email alerts
|

The mean platelet volume and neutrophil to lymphocyte ratio in obese and lean patients with polycystic ovary syndrome

Abstract: Our study demonstrated that MPV and NLR levels are increased despite similar hsCRP levels in patients with PCOS. However, we failed to demonstrate these differences in obese PCOS patients. Further studies with larger sample size are required to determine the significance of BMI in the inflammation of PCOS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 36 publications
7
39
1
1
Order By: Relevance
“…Ten of the eleven studies stratifying PCOS group according to BMI, revealed significantly higher circulating CRP in obese/overweight versus non-obese PCOS women, while one study showed no difference [96]. On the other hand, eight studies comparing between BMI strata in the control group reported higher CRP levels in the higher BMI group [51,59,78,87,98,100,115,122], while two studies revealed no difference [55,96]. Comparison between different BMI strata between PCOS women and controls is provided in the meta-analysis section below.…”
Section: Systematic Review 221 Crp Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Ten of the eleven studies stratifying PCOS group according to BMI, revealed significantly higher circulating CRP in obese/overweight versus non-obese PCOS women, while one study showed no difference [96]. On the other hand, eight studies comparing between BMI strata in the control group reported higher CRP levels in the higher BMI group [51,59,78,87,98,100,115,122], while two studies revealed no difference [55,96]. Comparison between different BMI strata between PCOS women and controls is provided in the meta-analysis section below.…”
Section: Systematic Review 221 Crp Resultsmentioning
confidence: 98%
“…To further investigate the effect of obesity as a main confounder on inflammatory status, we separately looked at eleven studies that stratified their participants according to BMI [51,55,59,66,78,87,96,98,100,115,122] and two studies that included only obese participants only [45,110] (Table 1). Ten of the eleven studies stratifying PCOS group according to BMI, revealed significantly higher circulating CRP in obese/overweight versus non-obese PCOS women, while one study showed no difference [96].…”
Section: Systematic Review 221 Crp Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted with patients who had PCOS, a negative correlation was detected between BMI, NLR and PLR 21 . In a study that was conducted by Yılmaz et al with obese patients who had PCOS, a positive correlation was detected between NLR and BMI 22 . In another study conducted by Aydın et al it was determined that NLR was higher and PLR was insignificant 23 .…”
Section: Discussionmentioning
confidence: 90%
“…In a previous study, women with PCOS had a higher MPV, neutrophil to lymphocyte ratio, neutrophil count, neutrophil to total leucocyte ratio, and basophil count compared with controls. 11 Yilmaz et al 11 showed that MPV and the neutrophil to lymphocyte ratio were significantly higher in women with PCOS, despite similar high-sensitivity C-reactive protein levels, compared with patients without PCOS. A positive correlation of high-sensitivity C-reactive protein levels and the WBC count and a negative correlation of MPV with BMI were also reported.…”
Section: Discussionmentioning
confidence: 99%